Orthodontic Traction of a Buccally Impacted Maxillary Canine with missing lateral: A case report - Shrestha, BK (Journal of Institute of Medicine Nepal, 2013)
A 14-year-old girl presented with complains of space in the right upper quadrant and teeth. On intra-oral examination, she had missing right upper permanent lateral and upper permanent canine had taken the place of lateral incisor. On the left upper qua had retained deciduous lateral incisor and canine. On radiographic examination, left permanent canine was impacted and was lying high up and there was no sign incisor. She had severe crowding in the lower arch with all permanent teeth pre deciduous lateral incisor and the canine were extracted and more than a year was for spontaneous eruption of permanent canine. As the spontaneous eruption of not occur, surgical exposure and orthodontic traction was done and canine was occlusion satisfactorily and converted into lateral. This experience proves that spontaneous eruption may take place in majority of cases after extraction of deciduous surgical exposure and orthodontic traction is also needed at times. This is very be such a case with missing lateral as this provides an opportunity to have natural tee artificial prosthesis in addition to having acceptable esthetics.